Blind Exchange With Mini-Pinning Technique Using the Tron Stent Retriever for Middle Cerebral Artery M2 Occlusion Thrombectomy in Acute Ischemic Stroke - Yoshimoto, Takeshi; Tanaka, Kanta; Koge, Junpei; Shiozawa, Masayuki; Yamagami, Hiroshi; Inoue, Manabu; Kamogawa, Naruhiko; Satow, Tetsu; Kataoka, Hiroharu; Toyoda, Kazunori; Ihara, Masafumi; Koga, Masatoshi (Frontiers in Neurology, 2021)
Introduction: The usefulness of the blind exchange with mini-pinning (BEMP) technique has recently been reported for mechanical thrombectomy in patients with stroke owing to medium vessel occlusion (MeVO). The Tron stent retriever can be delivered and deployed through a 0.0165-inch microcatheter. This retriever has potential as an effective and safe treatment for acute ischemic stroke (AIS) due to occlusion of the M2 segment of the middle cerebral artery. Here, we report the outcomes of the BEMP technique using Tron stent retrievers for M2 occlusion thrombectomy. Methods: Consecutive patients with AIS owing to M2 occlusion who underwent the BEMP technique using 2 × 15-mm or 4 × 20-mm Tron stent retrievers were included. The technique involves deploying a Tron stent retriever through a 0.0165-inch microcatheter followed by microcatheter removal and blind navigation of a 3MAX or 4MAX aspiration catheter over the bare Tron delivery wire until the aspiration catheter reaches the clot. A Tron stent retriever is inserted into the aspiration catheter like a cork, and subsequently pulled as a unit. We assessed procedural outcomes [first-pass expanded thrombolysis in cerebral infarction (eTICI) score 2c/3, and 2b/2c/3], safety outcomes [symptomatic intracranial hemorrhage (sICH)], and clinical outcomes (good outcome rate defined as modified Rankin Scale score 0–2 at 90 day, and mortality at 90 days). Results: Eighteen M2 vessels were treated in 15 patients (6 female, median age: 80 years, and median National Institutes of Health Stroke Scale score: 18). The BEMP technique was performed successfully in all cases. Whether to use a 3MAX or 4MAX catheter was determined by considering one of the following target vessels: dominant, non-dominant, or co-dominant M2 (3MAX, n = 9; 4MAX, n = 9). The first-pass eTICI 2c/3 and 2b/2c/3 rates were 47% (7/15) and 60% (9/15), respectively; sICH was not observed. Seven patients (47%) achieved good outcomes, and one patient (7%) died within 90 days. Conclusions: The Tron stent retriever was safely and effectively used in the BEMP technique for acute MCA M2 occlusion and can be combined with a 0.0165-inch microcatheter, which may be useful for treating MeVO, in general.